Adhesives, laminates, packaging materials

By using a follower containing polyester polyol and polyisocyanate compound, the problem of insufficient cooking resistance of the existing follower under high temperature and high pressure conditions is solved, and resistance to low molecular weight compounds is achieved in daily necessities, and the follower is realized. Excellent effect of cooking resistance and content resistance.

CN115667452BActive Publication Date: 2025-02-18DIC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180037174.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-16
Filing Date
2021-06-03
Publication Date
2025-02-18
Estimated Expiration
2041-06-03

AI Technical Summary

Technical Problem

When the existing adhesion agent faces high temperature and high pressure hot water spray cooking treatment in food packaging, the adhesion resistance is insufficient, and it is difficult to realize the adhesion agent with excellent content properties of low molecular weight compounds that require fragrance or surfactant resistance in daily necessities.

Method used

The polyol composition containing polyester polyol (A1) and the follower of the polyisocyanate compound (B1) is used, wherein the polyester polyol (A1) is generated by the reaction of a polycarboxylic acid with a polyol, which contains Tetrapolymeric acid improves the branch point concentration and flexibility of the hardened coating film of the adsorbent.

Benefits of technology

The adhesion agent has excellent cooking resistance and content resistance, ensuring the adhesion strength maintained in the presence of high-temperature environment and moisture and low molecular weight moving objects, and is suitable for packaging materials for food packaging and daily necessities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003957620300000261
    Figure GDA0003957620300000261
  • Figure GDA0003957620300000271
    Figure GDA0003957620300000271
Patent Text Reader

Abstract

The present invention provides an adhesive for lamination, a laminate, and a packaging material having excellent retort resistance and content resistance. An adhesive, a laminate, and a packaging material formed using the adhesive, wherein the adhesive comprises: a polyol composition (A) containing a polyester polyol (A1) and a polyisocyanate composition (B) containing a polyisocyanate compound (B1), wherein the polyester polyol (A1) is a reaction product of a composition containing a polycarboxylic acid and a polyol, and the polycarboxylic acid contains a tetrameric acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive, a laminated body obtained by using the adhesive, and a packaging material. Background Art

[0002] As packaging materials for food, medical products, cosmetics, daily necessities, etc., materials formed by multi-layer lamination and compounding of metal foils such as aluminum foil or metal vapor-deposited films with plastic films such as polyethylene, polypropylene, vinyl chloride, polyester, and nylon can be used. These laminates are laminates formed by appropriately combining various plastic films, metal vapor-deposited films, or metal foils according to the required characteristics in various uses and using adhesives to adhere them. As adhesives, generally, two-liquid curing adhesives (e.g., patent document 1) containing a polyol composition and a polyisocyanate composition can be used.

[0003] The adhesive can also be appropriately selected according to the contents, etc. For example, if it is used for food, in order to protect the contents from various circulation, storage such as refrigeration, or heat sterilization, etc., an adhesive with functions such as bag breaking strength, cold resistance, boiling resistance, and heat resistance when made into a packaging material can be selected. If it is used for daily necessities such as detergents, shampoos, and shower gels, an adhesive with excellent resistance to low molecular weight compounds such as fragrances or surfactants contained in the contents can be used.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-101422 Summary of the invention

[0007] Problems to be solved by the invention

[0008] The requirements for these properties of adhesives are increasing day by day. For example, in the field of food packaging, with the trend of improving dietary habits, the trend of improving food sterilization efficiency is rising, and the opportunities for hot water spray retort treatment to replace the existing hot water storage retort treatment are increasing. In hot water spray retort treatment, since the high-temperature and high-pressure hot water spray sometimes directly contacts the laminate, a higher level of retort resistance is required for the adhesive than before.

[0009] In addition, in recent years, as consumer preferences have changed, there have been more and more products with strong fragrances, that is, products containing more fragrances than before, and adhesives with better resistance to contents have been required.

[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a laminating adhesive having excellent retort resistance and content resistance.

[0011] Technical means of solving problems

[0012] The present inventors have found that the above-mentioned problems can be solved by using an adhesive comprising: a polyol composition (A) containing a polyester polyol (A1) and a polyisocyanate composition (B) containing a polyisocyanate compound (B1), wherein the polyester polyol (A1) is a reaction product of a composition comprising a polycarboxylic acid and a polyol, and the polycarboxylic acid comprises a tetrameric acid.

[0013] That is, the present invention relates to an adhesive comprising: a polyol composition (A) containing a polyester polyol (A1) which is a reaction product of a composition containing a polycarboxylic acid and a polyol, and a polyisocyanate composition (B) containing a polyisocyanate compound (B1), wherein the polyester polyol (A1) is a reaction product of a composition containing a polycarboxylic acid and a polyol, and the polycarboxylic acid contains a tetramer acid.

[0014] Effects of the Invention

[0015] According to the adhesive of the present invention, it is possible to provide an adhesive, a laminate, and a packaging material that are excellent in retort resistance and content resistance. DETAILED DESCRIPTION

[0016] <Adhesive>

[0017] The adhesive of the present invention comprises: a polyol composition containing a polyester polyol (A1) and a polyisocyanate composition (B) containing a polyisocyanate compound (B1), wherein the polyester polyol (A1) is a reaction product of a monomer composition containing a polycarboxylic acid and a polyol, and the polycarboxylic acid contains a tetramer acid. The adhesive of the present invention is described in detail below.

[0018] (Polyol composition (A))

[0019] The polyol composition (A) used in the adhesive of the present invention contains a polyester polyol (A1). The polyester polyol (A1) is a reaction product of a monomer composition containing a polycarboxylic acid and a polyol, and the polycarboxylic acid contains a tetramer acid as an essential component.

[0020] Tetramer acid is a product obtained by Diels-Alder reaction of unsaturated fatty acids represented by oleic acid or linoleic acid, and is a tetrafunctional carboxylic acid obtained by reacting unsaturated fatty acids contained in linseed oil fatty acids, tall oil fatty acids, soybean oil fatty acids, rice bran oil fatty acids, rapeseed oil fatty acids, sunflower oil fatty acids, and recovered oils of natural oils containing these fatty acids. It can be any one of acyclic, monocyclic, polycyclic, and aromatic ring types, or a combination of any two or more.

[0021] The reasons for the excellent heat resistance and content resistance of the adhesive of the present invention are speculated as follows. The carboxyl group of the tetramer acid is directly bonded to the saturated alkyl group, and the distance from the branch point to the reaction point (carboxyl group) is also long, so it is not easily affected by steric hindrance. In addition, it becomes a liquid at a relatively low temperature, and the reactivity of the carboxyl group of the tetramer acid is high, and it is preferentially consumed in the early stage of the esterification reaction. Therefore, the polyester polyol (A1) using the tetramer acid as a raw material becomes a polyester polyol (A1) containing a polyester polyol (a1) having a star-shaped branch structure centered on the tetramer acid. By using a polyol composition (A) containing such a polyester polyol (A1), the cured coating of the adhesive becomes a cured coating containing a large number of branch points derived from the polyester polyol (a1) and a high concentration of branch points. The branch points derived from the polyester polyol (a1) are difficult to decompose even in a high temperature environment or in the presence of moisture and low molecular weight migration products. Therefore, even in a high temperature environment or when the components derived from the contents migrate, the branch structure can be maintained to suppress the reduction of the bonding strength. That is, it is possible to obtain an adhesive having excellent heat resistance, retort resistance, and resistance to contents.

[0022] Furthermore, as described above, there is a distance from the branch point of tetramer acid to the reaction point, so the ester bond of polyester polyol (a1) will not be locally present near the branch point from tetramer acid. Therefore, even if the branch point concentration of the hardened coating is high, the flexibility can be maintained, and the adhesion of the films to each other is excellent, and the adhesion of relatively hard layers such as aluminum foil or aluminum vapor-deposited layer, inorganic oxide vapor-deposited layer and relatively soft layers such as resin film is also excellent. The adhesive layer can also be expected to prevent the aluminum vapor-deposited layer, the vapor-deposited layer of inorganic oxide, etc. from cracking or peeling. Even when the hardened coating is immersed in water, the molecular chain has not been cut once near the branch point, so it can be made into an adhesive with good hot water resistance.

[0023] Examples of the polycarboxylic acid other than the tetramer acid used for preparing the polyester polyol (A1) include aliphatic polycarboxylic acids such as malonic acid, ethylmalonic acid, dimethylmalonic acid, succinic acid, 2,2-dimethylsuccinic acid, succinic anhydride, alkenylsuccinic anhydride, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, maleic anhydride, itaconic acid, dimer acid, and trimer acid;

[0024] Alkyl esters of aliphatic polycarboxylic acids such as dimethyl malonate, diethyl malonate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, diethyl pimelate, diethyl sebacate, dimethyl fumarate, diethyl fumarate, dimethyl maleate, and diethyl maleate;

[0025] Alicyclic polycarboxylic acids such as 1,1-cyclopentanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, tetrahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, cyclohexane-1,2,4-tricarboxylic acid-1,2-anhydride, himic anhydride, and chlorendic anhydride;

[0026] Aromatic polycarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, phthalic anhydride, 1,4-naphthalene dicarboxylic acid, 2,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic anhydride, naphthalene dicarboxylic acid (naphthalic acid), 1,2,4-benzene trimectric acid, 1,2,4-benzene trimectric anhydride, pyromellitic acid, pyromellitic anhydride, biphenyl dicarboxylic acid, 1,2-bis (phenoxy) ethane-p,p'-dicarboxylic acid, benzophenone tetracarboxylic acid, benzophenone tetracarboxylic dianhydride, 5-sodium sulfoisophthalic acid, tetrachlorophthalic anhydride, and tetrabromophthalic anhydride;

[0027] Methyl esters of aromatic polycarboxylic acids such as dimethylterephthalic acid and dimethyl 2,6-naphthalenedicarboxylate can be used alone or in combination of two or more.

[0028] The polyol used to prepare the polyester polyol (A1) may be a diol or a trifunctional or higher polyol. Examples of the diol include aliphatic diols such as ethylene glycol, diethylene glycol, propylene glycol, 1,3-propylene glycol, 1,2,2-trimethyl-1,3-propylene glycol, 2,2-dimethyl-3-isopropyl-1,3-propylene glycol, 1,4-butanediol, 1,3-butanediol, 3-methyl-1,3-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,4-bis(hydroxymethyl)cyclohexane, 2,2,4-trimethyl-1,3-pentanediol, and dimer diol.

[0029] Ether diols such as polyoxyethylene glycol and polyoxypropylene glycol;

[0030] Modified polyether diols obtained by ring-opening polymerization of the aliphatic diols with various compounds containing cyclic ether bonds such as ethylene oxide, propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether;

[0031] Lactone polyester polyols obtained by polycondensation of the aliphatic diols with various lactones such as lactanoid and ε-caprolactone;

[0032] Bisphenols such as bisphenol A and bisphenol F;

[0033] Alkylene oxide adducts of bisphenols obtained by adding ethylene oxide, propylene oxide, etc. to bisphenols such as bisphenol A and bisphenol F, and the like.

[0034] The trifunctional or higher polyols include: aliphatic polyols such as trimethylolethane, trimethylolpropane, glycerol, hexanetriol, and pentaerythritol;

[0035] Modified polyether polyols obtained by ring-opening polymerization of the aliphatic polyols with various compounds containing cyclic ether bonds such as ethylene oxide, propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether;

[0036] Lactone polyester polyols obtained by polycondensation of the above-mentioned aliphatic polyols with various lactones such as ε-caprolactone, etc.

[0037] When the monomer composition includes a compound (b) in which the carbon number of the shortest methylene chain between functional groups is 6 or more and 20 or less, more specifically, an aliphatic polycarboxylic acid (b1) having multiple carboxyl groups and the carbon number of the shortest methylene chain between carboxyl groups is 6 or more and 20 or an aliphatic polyol (b2) having multiple hydroxyl groups and the carbon number of the shortest methylene chain between hydroxyl groups is 6 or more and 20 or less, the cured coating of the adhesive becomes softer and has better adhesion to the aluminum vapor deposition layer or the inorganic oxide layer, so it is preferred. The amount of such compound (b) can be appropriately adjusted according to the functions required by the adhesive or other monomers, and as an example, it is 0.1% to 35% by mass of the monomer composition. As such polycarboxylic acids (b1) and polyols (b2), castor oil, dimer diol, suberic acid, azelaic acid, sebacic acid, dimer acid, trimer acid, etc. Among them, dimer acid is preferred. Furthermore, the carbon atoms of the methylene chain do not include carbon atoms of the carboxyl group. In addition, when there is an alicyclic structure or an aromatic ring between two functional groups in addition to the methylene chain (for example, dimer acid), the carbon atoms forming these ring structures are not included in the methylene chain. When the polycarboxylic acid (b1) or the polyol (b2) has three or more functional groups, the carbon number of the methylene chain between the shortest functional groups is used.

[0038] As polycarboxylic acids and polyols other than tetramer acid for preparing polyester polyol (A1), it is also preferred to use pyromellitic acid, pyromellitic anhydride, sorbitol, pentaerythritol, dipentaerythritol, etc. These monomers can improve the branch point concentration of the cured coating of the adhesive in the same way as tetramer acid. On the other hand, the distance from the branch point to the reaction point of these monomers is short, and the ester bond is concentrated near the branch point, so unlike the case of using tetramer acid, the softness of the cured coating has a tendency to decrease. Therefore, it is preferred to use a polycarboxylic acid (b1) or polyol (b2) having a methylene chain with a carbon number of more than 6 and less than 20 between the functional groups together with these monomers. In the case of using sorbitol, polyester polyol (A1) is colored, and in the case of attaching importance to the use of appearance, it is preferably selected from pyromellitic acid, pyromellitic anhydride, dimer acid, pentaerythritol, dipentaerythritol.

[0039] The polyester polyol (A1) may be a polyester polyurethane polyol (A1') having polyisocyanate as an essential raw material in addition to the polycarboxylic acid and the polyol. Alternatively, the polyester polyol (A1) may be a mixture of the polyester polyol (A1) and the polyester polyurethane polyol (A1'). The polyisocyanate used to prepare the polyester polyurethane polyol (A1') may be the same as the polyisocyanate exemplified as the polyisocyanate compound (B1) described later, alone or in combination of two or more thereof.

[0040] The polyester polyurethane polyol (A1′) may be one obtained by synthesizing a polyester polyol as a precursor and then subjecting it to urethane elongation, or one obtained by reacting a monomer composition containing a polycarboxylic acid, a polyol, and a polyisocyanate all at once.

[0041] There is no particular restriction on the amount of tetramer acid to be formulated. For example, when the amount of tetramer acid to be formulated in the total amount of the monomer composition for synthesizing polyester polyol (A1) is 0.1% by mass or more, heat resistance and resistance to contents are easily improved and preferred. There is no particular restriction on the upper limit, but if it is too much, gelation is likely to occur when manufacturing polyester polyol (A1), and the manufacturing difficulty becomes higher, so it is preferably limited to less than 4.0% by mass of the total amount of the monomer composition. More preferably, it is 0.1% by mass or more and 2.0% by mass or less. Furthermore, when polyester polyol (A1) is polyester polyurethane polyol (A1'), the monomer composition includes polycarboxylic acid, polyol, and polyisocyanate used in the synthesis.

[0042] The number average molecular weight (Mn) of the polyester polyol (A1) is not particularly limited, and is, for example, 500 to 100,000, more preferably 1,000 to 50,000. In addition, the weight average molecular weight (Mw) is, for example, 1,000 to 300,000, more preferably 2,000 to 200,000. In this specification, the number average molecular weight (Mn) and the weight average molecular weight (Mw) are values ​​measured by gel permeation chromatography (GPC) under certain conditions.

[0043] Measurement device: HLC-8320GPC manufactured by Tosoh Corporation

[0044] Column: TSKgel 4000HXL, TSKgel 3000HXL, TSKgel2000HXL, TSKgel 1000HXL manufactured by Tosoh Corporation

[0045] Detector: RI (differential refractometer)

[0046] Data processing: Multi station GPC-8020 model II manufactured by Tosoh Corporation

[0047] Measurement conditions: column temperature 40°C

[0048] Solvent tetrahydrofuran

[0049] Flow rate 0.35ml / min

[0050] Standard: Monodisperse polystyrene

[0051] Sample: A sample (100 μl) obtained by filtering a tetrahydrofuran solution having a content of 0.2% by mass in terms of resin solid content through a microfilter.

[0052] The hydroxyl value of the polyester polyol (A1) is preferably in the range of 1 mgKOH / g to 150 mgKOH / g, more preferably 3 mgKOH / g or more and 100 mgKOH / g or less. In addition, the acid value of the polyester polyol (A1) is not particularly limited, and is preferably 10.0 mgKOH / g or less. The lower limit is not particularly limited, and as an example, it is 0.5 mgKOH / g or more. It can also be 0 mgKOH / g. The hydroxyl value and acid value can be measured by the method described in Japanese Industrial Standard (JIS)-K0070.

[0053] The polyol composition (A) may also contain a polyol (A2) other than the polyester polyol (A1). As the polyol (A2), the polyol (A2) exemplified as the polyol for preparing the polyester polyol (A1) can be cited. When the polyol composition (A) contains the polyol (A2), the amount of the polyester polyol (A1) is preferably 70 parts by mass or more, more preferably 80 parts by mass or more, and further preferably 90 parts by mass or more, relative to 100 parts by mass of the total amount of the polyester polyol (A1) and the polyol (A2).

[0054] (Polyisocyanate composition (B))

[0055] The polyisocyanate composition (B) contains a polyisocyanate compound (B1). The polyisocyanate compound (B1) is not particularly limited, and known compounds can be used. Examples of such polyisocyanate compounds (B1) include polyisocyanates having an aromatic structure in their molecular structures, such as tolylene diisocyanate, diphenylmethane diisocyanate, polymerized diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, and xylylene diisocyanate, and compounds obtained by modifying a portion of the NCO group of these polyisocyanates using carbodiimide;

[0056] Polyisocyanates having an alicyclic structure in the molecular structure, such as isophorone diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and 1,3-(isocyanatomethyl)cyclohexane;

[0057] Straight-chain aliphatic polyisocyanates such as 1,6-hexamethylene diisocyanate, 1,5-pentamethylene diisocyanate, lysine diisocyanate, and trimethylhexamethylene diisocyanate, and compounds obtained by modifying a part of the NCO group of these polyisocyanates with carbodiimide;

[0058] Isocyanurate forms of these polyisocyanates; allophanate forms of these polyisocyanates; biuret forms of these polyisocyanates; adduct forms of these polyisocyanates modified with trimethylolpropane; polyurethane polyisocyanates which are reaction products of these polyisocyanates and polyols, and the like.

[0059] When a polyurethane polyisocyanate is used as the polyisocyanate compound (B1), in terms of the balance between the cohesive force and the flexibility of the adhesive coating film, a polyurethane polyisocyanate obtained by reacting the polyisocyanate with a polyol at a ratio of the equivalent ratio [NCO] / [OH] of isocyanate group to hydroxyl group of 1.5 to 5.0 is preferred.

[0060] Examples of the polyol used for preparing the polyurethane polyisocyanate include: chain aliphatic diols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, methylpentanediol, dimethylbutanediol, butylethylpropylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, and bishydroxyethoxybenzene;

[0061] Alicyclic diols such as 1,4-cyclohexanediol and 1,4-cyclohexanedimethanol;

[0062] Trifunctional or tetrafunctional aliphatic alcohols such as glycerol, trimethylolpropane, and pentaerythritol;

[0063] Bisphenols such as bisphenol A, bisphenol F, hydrogenated bisphenol A, hydrogenated bisphenol F, etc.

[0064] dimer diol;

[0065] A polyether polyol obtained by addition polymerization of ethylene oxide, propylene oxide, butylene oxide, styrene oxide, epichlorohydrin, tetrahydrofuran, cyclohexylene and other alkylene oxides in the presence of a polymerization initiator such as the diol, trifunctional or tetrafunctional aliphatic alcohol;

[0066] A polyester polyol (1) obtained by ring-opening polymerization of a cyclic ester compound such as propiolactone, butyrolactone, ε-caprolactone, ζ-valerolactone, β-methyl-ζ-valerolactone and the like and a reaction product of the diol or trifunctional or tetrafunctional aliphatic alcohol;

[0067] A polyester polyol (2) obtained by reacting a polyol such as the linear aliphatic diol, alicyclic diol, dimer diol, bisphenol or the polyether polyol with a polycarboxylic acid;

[0068] A polyester polyol (3) obtained by reacting the trifunctional or tetrafunctional aliphatic alcohol with a polycarboxylic acid;

[0069] A polyester polyol (4) obtained by reacting a difunctional polyol, the trifunctional or tetrafunctional aliphatic alcohol and a polycarboxylic acid;

[0070] Polymers of hydroxy acids such as dimethylolpropionic acid and castor oil fatty acid, i.e. polyester polyols (5);

[0071] A mixture of the polyester polyol (1), polyester polyol (2), polyester polyol (3), polyester polyol (4), polyester polyol (5) and polyether polyol;

[0072] Castor oil-based polyols such as castor oil, castor hardened oil which is a hydrogenated product of castor oil, and 5 to 50 mol of alkylene oxide adducts of castor oil can be used alone or in combination of two or more.

[0073] As the polycarboxylic acid used for preparing the polyester polyols (2) to (5), the same polycarboxylic acid as that used for preparing the polyester polyol (A1) can be used.

[0074] The polyisocyanate compound (B1) is preferably an isocyanurate, allophanate, biuret or adduct of a polyisocyanate having an aromatic structure in its molecular structure, a compound in which a part of the NCO group of a polyisocyanate having an aromatic structure in its molecular structure is modified with carbodiimide, or a polyisocyanate having an alicyclic structure in its molecular structure. More preferred are isocyanurate, allophanate, biuret or adduct of tolylene diisocyanate, 1,6-hexamethylene diisocyanate, xylylene diisocyanate or isophorone diisocyanate.

[0075] (Other ingredients of adhesive)

[0076] The adhesive of the present invention may also contain components other than the above components. These components may be contained in either or both of the polyol composition (A) or the polyisocyanate composition (B), or may be prepared separately from these components and mixed with the polyol composition (A) and the polyisocyanate composition (B) just before the adhesive is applied. Each component is described below.

[0077] (Organic Solvent)

[0078] The adhesive of the present invention may be in any form of solvent-based or solvent-free. The "solvent-based" adhesive described in the present invention refers to a form used in a method in which the adhesive is applied to a substrate and then heated in an oven or the like to volatilize the organic solvent in the coating film and then bonded to another substrate, the so-called dry lamination method. Either or both of the polyol composition (A) and the polyisocyanate composition (B) contain an organic solvent that can dissolve (dilute) the constituent components of the polyol composition (A) and the constituent components of the polyisocyanate composition (B) used in the present invention.

[0079] Examples of the organic solvent include esters such as ethyl acetate, butyl acetate, and cellosolve acetate, ketones such as acetone, methyl ethyl ketone, isobutyl ketone, and cyclohexanone, ethers such as tetrahydrofuran and dioxane, aromatic hydrocarbons such as toluene and xylene, halogenated hydrocarbons such as methylene chloride and 1,2-dichloroethane, dimethyl sulfoxide, and dimethylsulfonyl diamide. The organic solvent used as a reaction medium when producing the constituent components of the polyol composition (A) or the polyisocyanate composition (B) may also be used as a diluent during coating.

[0080] In this specification, the "solvent-free" adhesive refers to the form of the adhesive used in the method of laminating with other substrates without applying the adhesive to the substrate and then heating it in an oven to volatilize the solvent, which is a so-called solvent-free lamination method. In the case where the constituent components of the polyol composition (A) or the polyisocyanate composition (B) cannot be completely removed, or the organic solvent used as a reaction medium in the manufacture of the raw materials thereof and a trace amount of organic solvent remains in the polyol composition (A) or the polyisocyanate composition (B), it is understood that the organic solvent is substantially not included. In addition, in the case where the polyol composition (A) contains a low molecular weight alcohol, the low molecular weight alcohol reacts with the polyisocyanate composition (B) to become a part of the coating film, so it does not need to be volatilized after coating. Therefore, this form is also regarded as a solvent-free adhesive, and the low molecular weight alcohol is not regarded as an organic solvent.

[0081] (catalyst)

[0082] The adhesive of the present invention can be used to promote the curing reaction by using a catalyst as needed. The catalyst is not particularly limited as long as it is a catalyst that promotes the urethanization reaction of the polyol composition (A) and the polyisocyanate composition (B), and examples thereof include metal catalysts, amine catalysts, aliphatic cyclic amide compounds, titanium chelate complexes, and the like.

[0083] As metal catalysts, metal complex catalysts, inorganic metal catalysts, and organic metal catalysts can be cited. As metal complex catalysts, acetylacetonate salts of metals selected from the group consisting of Fe (iron), Mn (manganese), Cu (copper), Zr (zirconium), Th (thorium), Ti (titanium), Al (aluminum), and Co (cobalt), such as iron acetylacetonate, manganese acetylacetonate, copper acetylacetonate, zirconium acetylacetonate, etc. can be cited. In terms of toxicity and catalyst activity, iron acetylacetonate (Fe(acac)3) or manganese acetylacetonate (Mn(acac)2) is preferred.

[0084] Examples of the inorganic metal catalyst include catalysts selected from Sn, Fe, Mn, Cu, Zr, Th, Ti, Al, Co and the like.

[0085] Examples of the organometallic catalyst include organozinc compounds such as zinc octylate, zinc neodecanoate, and zinc naphthenate; organotin compounds such as stannous diacetate, stannous dioctylate, stannous dioleate, stannous dilaurate, dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin oxide, and dibutyltin dichloride; organonickel compounds such as nickel octylate and nickel naphthenate; organocaloric compounds such as cobalt octylate and cobalt naphthenate; organobismuth compounds such as bismuth octylate, bismuth neodecanoate, and bismuth naphthenate; and titanium compounds such as tetraisopropoxy titanate, dibutyltitanium dichloride, tetrabutyl titanate, and butoxytitanium trichloride.

[0086] Examples of the amine catalyst include triethylenediamine, 2-methyltriethylenediamine, quinuclidine, 2-methylquinuclidine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethylpropylenediamine, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N',N",N"-pentamethyl-(3-aminopropyl)ethylenediamine, N,N,N',N",N"-pentamethyldipropylenetriamine, N,N,N',N'-tetramethylhexamethylenediamine, bis(2-dimethylaminoethyl)ether, dimethylethanolamine, dimethylisopropanolamine, dimethylaminoethoxyethanol, N,N-dimethyl-N'-(2-hydroxyethyl)ethylenediamine, N,N-dimethyl-N'-(2-hydroxyethyl)propylenediamine, bis(dimethyl 1,3,5-tris(N,N-dimethylaminopropyl)hexahydro-S-triazine, 1,8-diazabicyclo[5.4.0]undecene-7, N-methyl-N'-(2-dimethylaminoethyl)piperazine, N,N'-dimethylpiperazine, dimethylcyclohexylamine, N-methylmorpholine, N-ethylmorpholine, 1-methylimidazole, 1,2-dimethylimidazole, 1-isobutyl-2-methylimidazole, 1-dimethylaminopropylimidazole, N,N-dimethylhexanolamine, N-methyl-N'-(2-hydroxyethyl)piperazine, 1-(2-hydroxyethyl)imidazole, 1-(2-hydroxypropyl)imidazole, 1-(2-hydroxyethyl)-2-methylimidazole, 1-(2-hydroxypropyl)-2-methylimidazole, etc.

[0087] Examples of the aliphatic cyclic amide compound include δ-valerolactam, ε-caprolactam, ω-enantholactam, η-capryllactam, β-propiolactam, etc. Among these, ε-caprolactam is more effective in accelerating hardening.

[0088] The titanium chelate complex is a compound whose catalyst activity can be enhanced by ultraviolet irradiation. From the aspect of excellent curing acceleration effect, the titanium chelate complex having aliphatic diketone or aromatic diketone as a ligand is preferred. In addition, in the present invention, from the aspect of more significant effect of the present invention, the titanium chelate complex having an alcohol having 2 to 10 carbon atoms as a ligand other than aromatic diketone or aliphatic diketone is preferred.

[0089] These catalysts may be used alone or in combination of two or more. The amount of the catalyst is preferably 0.001 to 3 parts by mass, more preferably 0.01 to 2 parts by mass, relative to 100 parts by mass of the total solid content of the polyol composition (A) and the polyisocyanate composition (B).

[0090] (pigment)

[0091] The adhesive of the present invention may also contain a pigment as required. There is no particular limitation on the pigment used, and examples thereof include body pigments, white pigments, black pigments, gray pigments, red pigments, brown pigments, green pigments, blue pigments, metal powder pigments, luminescent pigments, pearl pigments and other organic or inorganic pigments, and plastic pigments, etc., as described in "Paint Raw Materials Handbook 1970" (edited by Japan Paint Industry Association).

[0092] Examples of the extender pigment include precipitated barium sulfate, chalk, precipitated calcium carbonate, calcium hydrogen carbonate, calcite, alumina white, silicon dioxide, hydrous micropowdered silicon dioxide (white carbon), ultrafine anhydrous silicon dioxide (Aerosil), silica sand (silica sand), talc, precipitated magnesium carbonate, bentonite, clay, kaolinite, and loess.

[0093] Specific examples of organic pigments include: various insoluble azo pigments such as benzidine yellow, fast yellow, and lake red 4R; soluble azo pigments such as lake red C, carmine 6B, and bordeaux 10; various (copper) phthalocyanine pigments such as phthalocyanine blue and phthalocyanine green; various basic dyeing lakes such as rhodamine lake and methyl violet lake; various mordant dye pigments such as quinoline lake and fast sky blue; various building dye pigments such as anthraquinone pigments, thioindigo pigments, and perinone pigments; various quinacridone pigments such as Cinquasia Red B; various dioxazine pigments such as dioxazine violet; various condensed azo pigments such as Cromophtal; aniline black, etc.

[0094] Examples of inorganic pigments include: various chromates such as yellow lead, zinc chromate, and molybdenum orange; various ferrocyanides such as Prussian blue; various metal oxides such as titanium oxide, zinc flower, mapico yellow, iron oxide, red iron, chromium oxide green, and zirconium oxide; various sulfides or selenides such as cadmium yellow, cadmium red, and mercuric sulfide; various sulfates such as barium sulfate and lead sulfate; various silicates such as calcium silicate and ultramarine blue; various carbonates such as calcium carbonate and magnesium carbonate; various phosphates such as cobalt violet and manganese violet; various metal powder pigments such as aluminum powder, gold powder, silver powder, copper powder, bronze powder, and brass powder; flake pigments and mica / flake pigments of these metals; metallic pigments or pearlescent pigments such as mica / flake pigments coated with metal oxides and mica-like iron oxide pigments; graphite, carbon black, and the like.

[0095] Examples of the plastic pigment include "GRANDOLL PP-1000" and "PP-2000S" manufactured by DIC Corporation.

[0096] The pigment to be used may be appropriately selected depending on the purpose. For example, inorganic oxides such as titanium oxide and zinc white are preferably used as white pigments, and carbon black is preferably used as black pigments in terms of excellent durability, weather resistance, and design properties.

[0097] The amount of the pigment added is, for example, 1 to 400 parts by mass based on 100 parts by mass of the total solid content of the polyol composition (A) and the polyisocyanate composition (B), and is more preferably 10 to 300 parts by mass in order to improve adhesion and blocking resistance.

[0098] (Adhesion Accelerator)

[0099] The adhesive of the present invention may contain an adhesion accelerator. Examples of the adhesion accelerator include coupling agents such as silane coupling agents, titanate coupling agents, and aluminum coupling agents, and epoxy resins.

[0100] Examples of the silane coupling agent include aminosilanes such as γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethyldimethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane; epoxysilanes such as β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane; vinylsilanes such as vinyltri(β-methoxyethoxy)silane, vinyltriethoxysilane, vinyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane; hexamethyldisilazane, γ-mercaptopropyltrimethoxysilane, and the like.

[0101] Examples of the titanate coupling agent include tetraisopropoxytitanium, tetra-n-butoxytitanium, butyl titanate dimer, tetrastearyl titanate, titanium acetylacetonate, tetraoctanediol titanate, and tetrastearyl titanium.

[0102] Examples of the aluminum coupling agent include acetoalkoxyaluminum diisopropylate and the like.

[0103] Examples of the epoxy resin include various epoxy resins generally available on the market such as epibis type, novolac type, β-methyl epichloro type, cyclic oxirane type, glycidyl ether type, glycidyl ester type, polyglycol ether type, glycol ether type, epoxidized fatty acid ester type, polycarboxylic acid ester type, aminoglycidyl type, and resorcinol type; and compounds such as triglycidyl tris(2-hydroxyethyl)isocyanurate, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, acrylic acid glycidyl ether, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether, phenol glycidyl ether, p-tert-butylphenyl glycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, methacrylate glycidyl ether, and butyl glycidyl ether.

[0104] (Other additives)

[0105] In addition to the above-mentioned components, the adhesive of the present invention may also contain a leveling agent, inorganic microparticles such as colloidal silica or alumina sol, organic microparticles of polymethyl methacrylate, a defoaming agent, a sag preventing agent, a wetting dispersant, a viscosity adjusting agent, an ultraviolet absorber, a metal deactivator, a peroxide decomposer, a flame retardant, a reinforcing agent, a plasticizer, a lubricant, a rust inhibitor, a fluorescent whitening agent, an inorganic heat absorber, a flame retardant, an antistatic agent, a dehydrating agent, a known conventional thermoplastic elastomer, a tackifier, a phosphoric acid compound, a melamine resin, a reactive elastomer, etc. The amount of these additives can be appropriately adjusted within the desired range that does not impair the adhesive of the present invention.

[0106] <Laminated body>

[0107] The laminate of the present invention can be obtained by laminating a plurality of films or papers by dry lamination or solvent-free lamination using the adhesive of the present invention. The film used is not particularly limited, and the film can be appropriately selected according to the purpose. For example, as food packaging, polyolefin films such as polyethylene terephthalate (PET) film, polystyrene film, polyamide film, polyacrylonitrile film, polyethylene film (LLDPE: low-density polyethylene film, HDPE: high-density polyethylene film) or polypropylene film (CPP: unstretched polypropylene film, OPP: biaxially stretched polypropylene film), polyvinyl alcohol film, ethylene-vinyl alcohol copolymer film, etc. can be listed.

[0108] The film may also be a film subjected to a stretching treatment. As a stretching treatment method, generally, after the resin is melt-extruded by an extrusion film-making method or the like to form a sheet, simultaneous biaxial stretching or successive biaxial stretching is performed. In addition, in the case of successive biaxial stretching, generally, a longitudinal stretching treatment is first performed, and then a transverse stretching is performed. Specifically, a method of combining longitudinal stretching using a speed difference between rollers with a transverse stretching using a tenter is mostly adopted.

[0109] Alternatively, a film having a deposited layer of a metal such as aluminum, a metal oxide such as silicon dioxide or aluminum oxide, or a gas barrier layer containing polyvinyl alcohol or an ethylene / vinyl alcohol copolymer, vinylidene chloride, etc. can also be used in combination. By using such a film, a laminate having a barrier property against water vapor, oxygen, alcohol, inert gas, volatile organic matter (fragrance), etc. can be produced.

[0110] More specific examples of the structure of the laminate include:

[0111] (1) Base film 1 / Adhesive layer 1 / Sealant film

[0112] (2) Base film 1 / Adhesive layer 1 / Metal-deposited unstretched film

[0113] (3) Base film 1 / Adhesive layer 1 / Metal-deposited stretched film

[0114] (4) Transparent vapor-deposited stretched film / adhesive layer 1 / sealant film

[0115] (5) Base film 1 / Adhesive layer 1 / Base film 2 / Adhesive layer 2 / Sealant film

[0116] (6) Base film 1 / Adhesive layer 1 / Metal-deposited stretched film / Adhesive layer 2 / Sealant film

[0117] (7) Base film 1 / Adhesive layer 1 / Transparent vapor-deposited stretched film / Adhesive layer 2 / Sealant film

[0118] (8) Base film 1 / Adhesive layer 1 / Metal layer / Adhesive layer 2 / Sealant film

[0119] (9) Base film 1 / Adhesive layer 1 / Base film 2 / Adhesive layer 2 / Metal layer / Adhesive layer 3 / Sealant film

[0120] (10) Base film 1 / adhesive layer 1 / metal layer / adhesive layer 2 / base film 2 / adhesive layer 3 / sealant film, etc., but the present invention is not limited thereto.

[0121] As the substrate film 1 that can be used in the structure (1), OPP film, PET film, nylon film (hereinafter referred to as Ny film) and the like can be cited. In addition, as the substrate film 1, a substrate film that has been coated for the purpose of improving gas barrier properties or ink receptivity when setting a printed layer described later can also be used. As commercially available products of the substrate film 1 that has been coated, K-OPP film or K-PET film can be cited. The adhesive layer 1 is a hardened coating of the adhesive of the present invention. As sealant films, CPP films, LLDPE films and the like can be cited. A printed layer can also be set on the surface of the adhesive layer 1 side of the substrate film 1 (the surface of the adhesive layer 1 side of the coating layer when a coated substrate film is used as the substrate film 1). The printed layer is formed by various printing inks such as gravure ink, flexographic ink, flat ink, orifice ink, and inkjet ink, and by a general printing method previously used for printing on polymer films.

[0122] As the base film 1 used in the structure (2) and the structure (3), OPP film or PET film can be cited. The adhesive layer 1 is a cured coating film of the adhesive of the present invention. As the metal-deposited unstretched film, a VM-CPP film in which a metal such as aluminum is deposited on a CPP film can be used, and as the metal-deposited stretched film, a VM-OPP film in which a metal such as aluminum is deposited on an OPP film can be used. As in the structure (1), a printed layer can be provided on the surface of the base film 1 on the adhesive layer 1 side.

[0123] As the transparent vapor-deposited stretched film used in structure (4), there can be cited films on which silica or alumina is vapor-deposited on OPP film, PET film, nylon film, etc. For the purpose of protecting an inorganic vapor-deposited layer of silica or alumina, a film coated on a vapor-deposited layer can also be used. Adhesive layer 1 is a hardened coating film of the adhesive of the present invention. The sealant film can be the same sealant film as that of structure (1). A printed layer can also be provided on the surface of the adhesive layer 1 side of the transparent vapor-deposited stretched film (the surface of the adhesive layer 1 side of the coating layer when a film coated on an inorganic vapor-deposited layer is used). The method for forming the printed layer is the same as that of structure (1).

[0124] As the substrate film 1 used in the structure (5), PET film and the like can be cited. As the substrate film 2, nylon film and the like can be cited. At least one of the adhesive layer 1 and the adhesive layer 2 is a cured coating film of the adhesive of the present invention. The sealant film can be the same sealant film as that of the structure (1). A printed layer can also be provided on the surface of the substrate film 1 on the adhesive layer 1 side as in the structure (1).

[0125] As the substrate film 1 of the structure (6), the same substrate film 1 as the structure (2) and the structure (3) can be cited. As the metal vapor-deposited stretched film, VM-OPP film or VM-PET film in which metal vapor deposition such as aluminum is performed on OPP film or PET film can be cited. At least one of the adhesive layer 1 and the adhesive layer 2 is a hardened coating film of the adhesive of the present invention. The sealant film can be the same sealant film as the structure (1). A printed layer can also be provided on the surface of the substrate film 1 on the side of the adhesive layer 1 in the same manner as the structure (1).

[0126] As the substrate film 1 of the structure (7), a PET film or the like can be cited. As the transparent vapor-deposited stretched film, the same transparent vapor-deposited stretched film as that of the structure (4) can be cited. At least one of the adhesive layer 1 and the adhesive layer 2 is a hardened coating film of the adhesive of the present invention. The sealant film can be the same sealant film as that of the structure (1). A printed layer can also be provided on the surface of the substrate film 1 on the adhesive layer 1 side as in the structure (1).

[0127] As the base film 1 of the structure (8), PET film and the like can be cited. As the metal layer, aluminum foil and the like can be cited. At least one of the adhesive layer 1 and the adhesive layer 2 is a cured coating film of the adhesive of the present invention. The sealant film can be the same sealant film as that of the structure (1). A printed layer can also be provided on the surface of the base film 1 on the adhesive layer 1 side in the same manner as in the structure (1).

[0128] As the substrate film 1 of the structure (9) and the structure (10), PET film and the like can be cited. As the substrate film 2, nylon film and the like can be cited. As the metal layer, aluminum foil and the like can be cited. At least one of the adhesive layer 1, the adhesive layer 2, and the adhesive layer 3 is a cured coating film of the adhesive of the present invention. The sealant film can be the same sealant film as that of the structure (1). A printed layer can also be provided on the surface of the substrate film 1 on the adhesive layer 1 side in the same manner as in the structure (1).

[0129] When the laminate of the present invention contains at least one of a metal vapor-deposited film, a transparent vapor-deposited film, and a metal layer, the adhesive layer in contact with the metal vapor-deposited layer, the transparent vapor-deposited layer, and the metal layer is preferably a cured coating film of the adhesive of the present invention.

[0130] When the adhesive of the present invention is a solvent type, the adhesive of the present invention is applied to a film material as a substrate using a roller such as a gravure roller, and after the organic solvent is volatilized by heating in an oven or the like, another substrate is attached to obtain the laminate of the present invention. It is preferred to perform an aging treatment after lamination. The aging temperature is preferably room temperature to 80° C., and the aging time is preferably 12 hours to 240 hours.

[0131] When the adhesive of the present invention is a solvent-free type, the adhesive of the present invention preheated to about 40°C to 100°C is applied to a film material as a substrate using a roller such as a gravure roller, and then another substrate is immediately attached to obtain the laminate of the present invention. It is preferred to perform an aging treatment after lamination. The aging temperature is preferably room temperature to 70°C, and the aging time is preferably 6 hours to 240 hours.

[0132] When the adhesive of the present invention is used as an auxiliary adhesive, the auxiliary adhesive of the present invention is applied to a film material as a substrate using a roller such as a gravure roll, and after the organic solvent is volatilized by heating in an oven or the like, the molten polymer material is laminated using an extruder to obtain the laminate of the present invention.

[0133] The amount of adhesive applied can be adjusted appropriately. In the case of a solvent-based adhesive, for example, the solid content is 1 g / m 2 Above and 10g / m 2 Below, preferably 2g / m 2 Above and 5g / m 2 In the case of a solvent-free adhesive, the coating amount of the adhesive is, for example, 1 g / m 2 Above and 5g / m 2 Below, preferably 1g / m 2 Above and 3g / m 2 the following.

[0134] When the adhesive of the present invention is used as an auxiliary adhesive, the coating amount is, for example, 0.1 g / m 2 Above and 2g / m 2 Below (solid content).

[0135] The laminate of the present invention may further contain other films or substrates in addition to the structures (1) to (10). As other substrates, in addition to the stretched film, unstretched film, and transparent vapor-deposited film, porous substrates such as paper, wood, and leather described later may also be used. The adhesive used when bonding other substrates may or may not be the adhesive of the present invention.

[0136] As paper, known paper substrates can be used without particular limitation. Specifically, natural fibers for papermaking such as wood pulp can be used and produced using known papermaking machines, and the papermaking conditions are not particularly specified. As natural fibers for papermaking, wood pulps such as conifer pulp and broadleaf pulp, non-wood pulps such as Manila hemp pulp, sisal pulp, and flax pulp, and pulps chemically modified from these pulps can be cited. As the type of pulp, chemical pulp, ground pulp, chemical ground wood pulp, thermomechanical pulp, etc. formed by sulfate digestion, acid / neutral / alkaline sulfite digestion, sodium salt digestion, etc. can be used.

[0137] In addition, various commercially available high-quality papers or coated papers, backing papers, impregnated papers, card papers or paperboards can also be used. In addition, a printed layer can also be provided on the outer surface or inner surface side of the paper layer as required.

[0138] The "other layers" may also contain known additives or stabilizers, such as antistatic agents, easy-adhesion coating agents, plasticizers, lubricants, antioxidants, etc. In addition, in order to improve the adhesion when stacked with other materials, the "other layers" may also be "other layers" in which the surface of the film is pre-treated by corona treatment, plasma treatment, ozone treatment, chemical treatment, solvent treatment, etc.

[0139] The laminate of the present invention can be preferably used for various purposes, such as packaging materials or lid materials for food or medicines, daily necessities, paper tableware such as paper straws or napkins, paper spoons, paper plates, and paper cups, wall-protecting materials, roofing materials, solar cell panel materials, battery packaging materials, window materials, outdoor flooring materials, lighting protection materials, automobile components, billboards, posters and other outdoor industrial uses, decorative sheets used in methods of simultaneous decoration by injection molding, and packaging materials for liquid laundry detergents, liquid kitchen detergents, liquid bath detergents, liquid bath soaps, liquid shampoos, liquid conditioners, etc.

[0140] In particular, when a retort treatment is performed, if the laminate is a laminate in which the Ny film and the aluminum foil are bonded via an adhesive layer, peeling easily occurs between these layers. Therefore, by bonding the Ny film and the aluminum foil using the adhesive of the present invention, a laminate having excellent retort resistance can be obtained.

[0141] As a more specific structural example, there can be listed: PET film / Ny film / aluminum foil / CPP film, PET film / aluminum foil / Ny film / CPP film, Ny film / aluminum foil / Ny film / CPP film, etc., and the Ny film and the aluminum foil are laminated using the adhesive of the present invention. Other films can be laminated using a general adhesive, or they can be laminated using the adhesive of the present invention. Of course, a printed layer can also be provided at an appropriate position of the laminate.

[0142] In the case where resistance to contents is required and in the case of a laminate containing a barrier layer such as an aluminum foil, an aluminum vapor-deposited layer, or an inorganic oxide layer, it is preferred to use the adhesive of the present invention in the adhesive layer located closest to the barrier layer side among the adhesive layers provided between the barrier layer and the sealant layer. Components derived from the contents migrating from the sealant side are retained near the barrier layer, so the adhesive layer closest to the barrier layer is easily degraded by the influence of the contents. Therefore, by using the adhesive of the present invention, degradation of the adhesive layer caused by the contents can be suppressed.

[0143] As a more specific structure, the following can be cited: transparent vapor-deposited PET film / adhesive layer based on the present invention / Ny film / sealant film, PET film / aluminum foil / adhesive layer based on the present invention / sealant film, PET film / aluminum foil / adhesive layer based on the present invention / PET film / sealant film, etc. As other structures, a laminate comprising Ny film / adhesive layer based on the present invention / aluminum vapor-deposited PET film / sealant film is also excellent in resistance to contents, so it is preferred. In these laminates, adhesive layers other than the adhesive layer based on the present invention can be bonded using a general adhesive, or can be bonded using the adhesive of the present invention. A printed layer is provided at an appropriate position of the laminate, but the record is omitted. In the case where higher strength is required for puncture resistance, etc., a transparent vapor-deposited Ny film can also be used instead of the aluminum vapor-deposited PET film and the transparent vapor-deposited PET film.

[0144] <Packaging materials>

[0145] The laminate of the present invention can be used as a multilayer packaging material for the purpose of protecting food or pharmaceuticals. When used as a multilayer packaging material, its layer structure can be changed according to the content, the use environment, and the use form. In addition, an easy-opening process or a resealable mechanism can also be appropriately provided in the packaging of the present invention.

[0146] The packaging material of the present invention can use the laminate of the present invention, and after the faces of the sealant films of the laminate are overlapped, the peripheral ends are heat-sealed and formed into a bag shape to obtain. As a bag making method, the following method can be cited: the laminate of the present invention is folded or overlapped so that the faces (faces of the sealant films) of its inner layer are facing each other and the peripheral ends are heat-sealed by forms such as side sealing type, two-sided sealing type, three-sided sealing type, four-sided sealing type, envelope pasting sealing type, hand-to-hand pasting sealing type, sealing type with pleats, flat bottom sealing type, square bottom sealing type, crease type, other heat sealing types, etc. The packaging material of the present invention can take various forms according to the content or the use environment and the use form. It can also be a self-supporting packaging material (self-supporting bag) etc. As a heat sealing method, known methods such as rod sealing, rotary roller sealing, belt sealing, impulse sealing, high frequency sealing, and ultrasonic sealing can be used.

[0147] After the opening of the packaging material of the present invention is filled with contents, the opening can be heat-sealed to manufacture a product using the packaging material of the present invention. Examples of the contents to be filled include: rice desserts, bean desserts, nuts, biscuits / cookies, wafer desserts, marshmallows, pies, half-baked cakes, candies, snacks such as fast food, bread, instant noodles, instant noodles, dry noodles, macaroni, aseptically packaged rice, vegetable porridge, porridge, packaged rice cakes, cereal foods and other staple foods, pickles, boiled beans, natto, soybean paste, frozen tofu, tofu, pickled mushrooms, konjac, wild vegetable processed products, jams, peanut butter, salads, frozen vegetables, potato processed products and other agricultural processed products, ham, bacon, sausages, chicken processed products, corned beef and other livestock processed products, fish ham / sausages, seafood cooked food, fish cakes, seaweed, seafood side dishes, dried loose fish, salted fish, smoked salmon (smoked salmon) processed seafood products such as salmon, mustard cod roe, peach, orange, pineapple, apple, pear, cherry and other fruit meats, corn, asparagus, mushrooms, onions, carrots, radish, potatoes and other vegetables, hamburger patties, meatballs, fried seafood, dumplings, croquettes and other frozen home-cooked dishes, refrigerated home-cooked dishes and other cooked foods, butter, margarine, cheese, cream, instant creamy powder, baby formula milk and other dairy products, liquid seasonings, retort curry, pet food and other foods.

[0148] In addition, as non-food products, it can also be used as various packaging materials such as cigarettes, disposable hot packs, infusion bags and other medicines, liquid laundry detergents, liquid kitchen detergents, liquid bath detergents, liquid bath soaps, liquid shampoos, liquid conditioners, cosmetics such as lotions or emulsions, vacuum insulation materials, batteries, etc.

[0149] Example

[0150] Hereinafter, the present invention will be described in more detail by listing specific synthesis examples and embodiments, but the present invention is not limited to these embodiments. In the following examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively.

[0151] <Synthesis of polyols>

[0152] (Synthesis example 1)

[0153] Into a polyester reaction vessel including a stirrer, a nitrogen inlet pipe, a Snyder tube, and a condenser, 6.4 parts of ethylene glycol, 22.3 parts of neopentyl glycol, 9.9 parts of 1,6-hexanediol, 17.3 parts of isophthalic acid, 21.3 parts of terephthalic acid, 11.9 parts of adipic acid, 0.2 parts of monomeric acid, 6.4 parts of dimer acid, 1.3 parts of trimer acid, 0.2 parts of tetramer acid, and 10 ppm of tetraisopropoxytitanium were added, and the mixture was slowly heated so that the temperature of the upper part of the distillation tube did not exceed 100°C, and the internal temperature was maintained at 260°C. After the acid value was lower than the specified value, the reaction was continued for another hour. The pressure was reduced to 30 mmHg and maintained for 3 hours to obtain an intermediate polyester polyol with a solid acid value of 0.6 mgKOH / g and a hydroxyl value of 10 mgKOH / g. The yield was 85%.

[0154] 3.6 parts by mass of isophorone diisocyanate were added to 100 parts by mass of the intermediate polyester polyol obtained, and the mixture was heated to 50°C to 90°C and subjected to urethanization reaction until the free NCO group was substantially eliminated, thereby obtaining a polyester polyurethane polyol having a hydroxyl value of 10 mgKOH / g. The mixture was diluted with ethyl acetate, and dibutyltin dilaurate was added to the polyester polyurethane polyol (solid content) in such a manner that the content was 200 ppm, thereby obtaining a polyester polyurethane polyol polyol A-1 having a solid content of 60%.

[0155] (Synthesis example 2)

[0156] Into a polyester reaction vessel including a stirrer, a nitrogen inlet pipe, a Snyder tube, and a condenser, 8.2 parts of ethylene glycol, 7.3 parts of diethylene glycol, 4.5 parts of neopentyl glycol, 18.1 parts of 1,6-hexanediol, 9.1 parts of isophthalic acid, 27.2 parts of terephthalic acid, 8.2 parts of adipic acid, 7.3 parts of sebacic acid, 0.2 parts of monomeric acid, 7.4 parts of dimer acid, 1.3 parts of trimer acid, 0.2 parts of tetramer acid, and 10 ppm of tetraisopropoxytitanium were added, and the mixture was slowly heated so that the temperature of the upper part of the distillation tube did not exceed 100°C, and the internal temperature was maintained at 260°C. After the acid value was lower than the specified value, the reaction was continued for another hour. The pressure was reduced to 30 mmHg and maintained for 3 hours to obtain an intermediate polyester polyol with a solid acid value of 0.6 mgKOH / g and a hydroxyl value of 14 mgKOH / g. The yield was 85%.

[0157] 1.4 parts by mass of toluene diisocyanate were added to 100 parts by mass of the intermediate polyester polyol obtained, and the mixture was heated to 50°C to 90°C and subjected to urethanization reaction until the free NCO group was substantially eliminated, thereby obtaining a polyester polyurethane polyol having a hydroxyl value of 14 mgKOH / g. The mixture was diluted with ethyl acetate, and dibutyltin dilaurate was added to the polyester polyurethane polyol (solid content) in such a manner that the content was 200 ppm, thereby obtaining a polyol A-2 having a polyester polyurethane polyol having a solid content of 60%.

[0158] (Synthesis example 3)

[0159] Into a polyester reaction vessel including a stirrer, a nitrogen inlet pipe, a Snyder tube, and a condenser, 13.2 parts of ethylene glycol, 17.5 parts of 1,6-hexanediol, 8.8 parts of isophthalic acid, 21.9 parts of terephthalic acid, 7.0 parts of adipic acid, 7.0 parts of sebacic acid, 0.6 parts of monomeric acid, 18.4 parts of dimer acid, 3.6 parts of trimer acid, 0.6 parts of tetramer acid, and 10 ppm of tetraisopropoxytitanium were added, and the mixture was slowly heated in such a way that the temperature of the upper part of the distillation tube did not exceed 100°C, and the internal temperature was maintained at 260°C. After the acid value was lower than the specified value, the reaction was continued for another hour. The pressure was reduced to 30 mmHg and maintained for 3 hours to obtain an intermediate polyester polyol with a solid acid value of 0.7 mgKOH / g and a hydroxyl value of 12 mgKOH / g. The yield was 84%.

[0160] 2.1 parts by mass of hexamethylene diisocyanate were added to 100 parts by mass of the intermediate polyester polyol obtained, and the mixture was heated to 50°C to 90°C and subjected to urethanization reaction until the free NCO group substantially disappeared, thereby obtaining a polyester polyurethane polyol having a hydroxyl value of 12 mgKOH / g. The mixture was diluted with ethyl acetate, and dibutyltin dilaurate was added to the polyester polyurethane polyol (solid content) in such a manner that the content was 200 ppm, thereby obtaining a polyol A-3 having a polyester polyurethane polyol having a solid content of 60%.

[0161] (Synthesis Example 4)

[0162] Into a polyester reaction vessel including a stirrer, a nitrogen inlet pipe, a Snyder tube, and a condenser, 10.6 parts of ethylene glycol, 6.4 parts of 2-methyl-1,3-propanediol, 15.9 parts of 1,6-hexanediol, 10.6 parts of isophthalic acid, 21.2 parts of terephthalic acid, 8.5 parts of adipic acid, 4.2 parts of azelaic acid, 0.6 parts of monomeric acid, 17.5 parts of dimer acid, 3.3 parts of trimer acid, 0.6 parts of tetramer acid, and 10 ppm of tetraisopropoxytitanium were added, and the mixture was slowly heated so that the temperature of the upper part of the distillation tube did not exceed 100°C, and the internal temperature was maintained at 260°C. After the acid value was lower than the specified value, the reaction was continued for another hour. The pressure was reduced to 30 mmHg and maintained for 3 hours to obtain an intermediate polyester polyol with a solid acid value of 0.7 mgKOH / g and a hydroxyl value of 13 mgKOH / g. The yield was 84%.

[0163] 0.9 parts by mass of 4,4'-diphenylmethane diisocyanate was added to 100 parts by mass of the intermediate polyester polyol obtained, and the mixture was heated to 50°C to 90°C and subjected to urethanization reaction until the free NCO group was substantially eliminated, thereby obtaining a polyester polyurethane polyol having a hydroxyl value of 13 mgKOH / g. The mixture was diluted with ethyl acetate, and dibutyltin dilaurate was added to the polyester polyurethane polyol (solid content) in such a manner that the content was 200 ppm, thereby obtaining a polyol A-4 having a polyester polyurethane polyol having a solid content of 60%.

[0164] (Synthesis Example 5)

[0165] Into a polyester reaction vessel including a stirrer, a nitrogen inlet pipe, a Snyder tube, and a condenser, 14.7 parts of ethylene glycol, 5.9 parts of 2-methyl-1,3-propanediol, 14.7 parts of 1,6-hexanediol, 29.4 parts of isophthalic acid, 17.6 parts of adipic acid, 0.4 parts of monomer acid, 13.8 parts of dimer acid, 2.9 parts of trimer acid, 0.5 parts of tetramer acid, and 10 ppm of tetraisopropoxytitanium were added, and the mixture was slowly heated in such a way that the temperature of the upper part of the distillation tube did not exceed 100°C, and the internal temperature was maintained at 260°C. After the acid value was lower than the specified value, the reaction was continued for another hour. The pressure was reduced to 30 mmHg and maintained for 3 hours to obtain a polyester polyol with a solid acid value of 0.8 mgKOH / g and a hydroxyl value of 20 mgKOH / g. The yield was 85%. This was diluted with ethyl acetate, and dibutyltin dilaurate was added to the polyester polyol (solid content) so as to be 200 ppm, thereby obtaining a polyol A-5 having a polyester polyol solid content of 60%.

[0166] (Synthesis Example 6)

[0167] Into a polyester reaction vessel including a stirrer, a nitrogen inlet pipe, a Snyder tube, and a condenser, 13.9 parts of ethylene glycol, 23.2 parts of 1,6-hexanediol, 38.6 parts of isophthalic acid, 18.6 parts of azelaic acid, 0.1 parts of dimer acid, 4.2 parts of trimer acid, 1.1 parts of tetramer acid, and 10 ppm of tetraisopropoxytitanium were added, and the temperature of the upper part of the distillation tube was slowly heated so that the temperature did not exceed 100°C, and the internal temperature was maintained at 260°C. After the acid value was lower than the specified value, the reaction was continued for another hour. The pressure was reduced to 30 mmHg and maintained for 3 hours to obtain a polyester polyol with a solid acid value of 0.8 mgKOH / g and a hydroxyl value of 24 mgKOH / g. The yield was 85%.

[0168] 0.3 parts by mass of toluene diisocyanate was added to 100 parts by mass of the intermediate polyester polyol obtained, and the mixture was heated to 50°C to 90°C and subjected to urethanization reaction until the free NCO group substantially disappeared, thereby obtaining a polyester polyurethane polyol having a hydroxyl value of 24 mgKOH / g. The mixture was diluted with ethyl acetate, and dibutyltin dilaurate was added to the polyester polyurethane polyol (solid content) in such a manner that the content was 200 ppm, thereby obtaining a polyol A-6 having a polyester polyurethane polyol having a solid content of 50%.

[0169] (Synthesis Example 7)

[0170] Into a polyester reaction vessel including a stirrer, a nitrogen inlet pipe, a Snyder tube, and a condenser, 12.2 parts of ethylene glycol, 15.2 parts of neopentyl glycol, 10.1 parts of 1,6-hexanediol, 16.2 parts of isophthalic acid, 21.8 parts of terephthalic acid, 24.4 parts of adipic acid, and 10 ppm of tetraisopropoxytitanium were added, and the temperature of the upper part of the distillation tube was slowly heated so that the temperature did not exceed 100°C, and the internal temperature was maintained at 260°C. After the acid value was lower than the specified value, the reaction was continued for another hour. The pressure was reduced to 30 mmHg and maintained for 3 hours to obtain a polyester polyol with a solid acid value of 0.6 mgKOH / g and a hydroxyl value of 10 mgKOH / g. The yield was 86%. It was diluted with ethyl acetate, and dibutyltin dilaurate was added to the polyester polyol (solid content) in a manner of 200 ppm to obtain a polyol AH-1 with a solid content of 60% of the polyester polyol.

[0171] (Synthesis Example 8)

[0172] Into a polyester reaction vessel including a stirrer, a nitrogen inlet pipe, a Snyder tube, and a condenser, 10.3 parts of ethylene glycol, 3.6 parts of diethylene glycol, 25.8 parts of 1,6-hexanediol, 20.7 parts of isophthalic acid, 15.0 parts of terephthalic acid, 15.0 parts of adipic acid, 7.7 parts of sebacic acid, and 10 ppm of tetraisopropoxytitanium were added, and the temperature of the upper part of the distillation tube was slowly heated so that the temperature did not exceed 100°C, and the internal temperature was maintained at 260°C. After the acid value was lower than the specified value, the reaction was continued for another hour. The pressure was reduced to 30 mmHg and maintained for 3 hours to obtain a polyester polyol with a solid acid value of 0.8 mgKOH / g and a hydroxyl value of 20 mgKOH / g. The yield was 86%.

[0173] 1.5 parts by mass of toluene diisocyanate was added to 100 parts by mass of the intermediate polyester polyol obtained, and the mixture was heated to 50°C to 90°C and subjected to urethanization reaction until the free NCO group was substantially eliminated, thereby obtaining a polyester polyurethane polyol having a hydroxyl value of 19 mgKOH / g. The mixture was diluted with ethyl acetate, and dibutyltin dilaurate was added to the polyester polyurethane polyol (solid content) in such a manner that the content was 200 ppm, thereby obtaining a polyester polyurethane polyol polyol AH-2 having a solid content of 60%.

[0174] Tables 1 and 2 show the solid content hydroxyl value of each polyol and the blending amount (mass %) of the tetramer acid in the monomer composition for synthesizing the polyester polyol.

[0175] [Table 1]

[0176] A-1 A-2 A-3 A-4 A-5 Hydroxyl value (mgKOH / g) 10 14 12 13 20 Tetramer acid blending amount (mass %) 0.23 0.22 0.62 0.57 0.52

[0177] [Table 2]

[0178] A-6 AH-1 AH-2 Hydroxyl value (mgKOH / g) 24 10 19 Tetramer acid blending amount (mass %) 1.14 0 0

[0179] <Preparation of Adhesive>

[0180] (Example 1)

[0181] The adhesive of Example 1 was prepared using polyol A-1 and polyisocyanate B-1 (Takenate D-110N (NB), a trimethylolpropane adduct of xylylene diisocyanate, 75% nonvolatile matter, manufactured by Mitsui Chemicals, Inc.) in the formulation shown in Table 3.

[0182] (Example 2) to (Example 6)

[0183] The adhesives of Examples 2 to 6 were prepared in the same manner as in Example 1 except that the polyols, isocyanates and their blends used were changed to those shown in Tables 3 and 4. In addition, the polyisocyanate B-2 in the table is Desmodur L75, a trimethylolpropane adduct of toluene diisocyanate, manufactured by Covestro, and has a non-volatile content of 75%.

[0184] (Comparative Example 1), (Comparative Example 2)

[0185] Adhesives of Comparative Examples 1 and 2 were prepared in the same manner as in Example 1, except that the polyol, isocyanate, and their blends were changed to those shown in Table 4.

[0186] The amounts in the table are values ​​including solvents. KBM-403 is 3-glycidyloxypropyltrimethoxysilane (Shin-Etsu Chemical).

[0187] <Manufacturing of laminated body>

[0188] (Manufacturing of Laminated Body 1)

[0189] The adhesives of the examples and comparative examples were applied using a bar coater at a coating amount of 3.5 g / m 2 The ethyl acetate was volatilized and dried in a dryer set at 70 degrees. Next, the adhesive was attached to an aluminum foil having a thickness of 30 μm. The laminate was aged at 40°C for 3 days to obtain a laminate 1.

[0190] (Manufacturing of Laminated Body 2)

[0191] The adhesives of the examples and comparative examples were applied using a bar coater at a coating amount of 3.5 g / m 2 The adhesive was applied to a PET film having a thickness of 12 μm in the form of (solid content), and the ethyl acetate was volatilized and dried in a dryer. Next, the adhesive was bonded to a stretched nylon film having a thickness of 15 μm.

[0192] Next, the coating amount was 3.5 g / m 2 (Solid Content) The adhesive of the example or comparative example was applied to the nylon surface of the laminate, and the ethyl acetate was volatilized and dried in a dryer set at a temperature of 70 degrees. The adhesive was bonded to an aluminum foil having a thickness of 9 μm.

[0193] Next, the coating amount was 3.5 g / m 2The adhesive of the embodiment or comparative example was applied to the aluminum foil surface of the laminate, and the ethyl acetate was volatilized and dried in a dryer set at a temperature of 70 degrees. The adhesive was bonded to a CPP film having a thickness of 70 μm. The laminate was aged at 40° C. for 3 days to obtain a laminate 2.

[0194] (Manufacturing of Laminated Body 3)

[0195] The adhesives of the examples and comparative examples were applied using a bar coater at a coating amount of 3.5 g / m 2 The mixture was applied to a PET film having a thickness of 12 μm in the form of (solid content), and the ethyl acetate was volatilized and dried in a dryer set at a temperature of 70 degrees. Next, the adhesive was bonded to an aluminum foil having a thickness of 9 μm.

[0196] Next, the coating amount was 3.5 g / m 2 The adhesive of the example or comparative example was applied to the aluminum foil surface of the laminate, ethyl acetate was volatilized and dried in a dryer set at 70 degrees, and the adhesive was laminated to a 60 μm thick LLDPE film and aged at 40° C. for 3 days to obtain a laminate 3.

[0197] <Evaluation>

[0198] (Normal Adhesion)

[0199] The adhesion strength (N / 15 mm) between the PET film and aluminum of the laminate 1 was measured by a T-type peeling method using a tensile tester at 25°C with a peeling speed of 300 mm / min. The results are summarized in Tables 3 and 4.

[0200] (Thermal indirect force)

[0201] The adhesion strength (N / 15 mm) between the PET film and aluminum of the laminate 1 was measured at a free angle using a tensile tester at 100°C and a peeling speed of 3 mm / min.

[0202] (Retort resistance)

[0203] A test piece was cut out from the laminate 2, folded with the CPP film facing inward, and heat-sealed on three sides other than the raised crease with a width of 10 mm. Then, a 1.5 mm incision (notch) was set at any position of the heat-sealed end to make a test piece. 20 test pieces made in the same manner were set in a manner such that the notch of each test piece was located near the hot water shower nozzle of a shower-type steam sterilization device (manufactured by Nisaka Seisakusho, Flavor Ace), and steamed at 135°C for 30 minutes. The state of the test piece after steaming was evaluated as follows and summarized in Tables 3 and 4.

[0204] 5: Less than 3 peelings with a long diameter of less than 3 mm

[0205] 4: There are 3 or more but less than 5 peelings with a major diameter of 3 mm or less

[0206] 3: There are 5 or more but less than 10 peelings with a major diameter of 3 mm or less

[0207] 2: There are more than 10 peelings with a long diameter of less than 3 mm, or less than 5 peelings with a long diameter of more than 3 mm

[0208] 1: There are more than 5 peelings with a long diameter exceeding 3 mm

[0209] (Resistance to contents)

[0210] The laminate 3 was folded with the LLDPE film facing inward so that the contact area with the heat-sealed contents was 200 cm. 2 A pouch was made in the manner of . After filling with 20 ml of d-limonene (manufactured by Tokyo Chemical Industry), the pouch was heat-sealed and sealed, and allowed to stand at 40°C for 1 week. The state between the aluminum foil and the LLDPE film of the pouch returned to room temperature was evaluated as follows and summarized in Tables 3 and 4.

[0211] 5: No peeling

[0212] 4: Peeling less than 10 mm (long side) was observed only near the raised fold.

[0213] 3: Peeling of 10 mm or more (long side) was observed only near the raised fold 2: Peeling was observed in about half of the bags 1: Peeling was observed on the entire surface of the bag [Table 3]

[0214]

[0215] [Table 4]

[0216]

[0217] As is clear from Tables 3 and 4, the adhesive of the present invention is an adhesive having excellent normal bonding strength, hot bonding strength, retort resistance, and content resistance. On the other hand, the adhesive of the comparative example is inferior in retort resistance and content resistance compared to the adhesive of the example.

Claims

1. An adhesive, characterized in that Include: a polyol composition (A) comprising a polyester polyol (A1); and a polyisocyanate composition (B) containing a polyisocyanate compound (B1), The polyester polyol (A1) is a reaction product of a monomer composition comprising a polycarboxylic acid and a polyol, wherein the polycarboxylic acid comprises a tetramer acid. The amount of the tetramer acid in the monomer composition is 0.1 mass % or more and 4.0 mass % or less, and the adhesive is a two-component curing adhesive. 2 . The adhesive according to claim 1 , wherein the monomer composition contains a compound (b) in which the shortest methylene chain between functional groups has 6 to 20 carbon atoms. 3 . The adhesive according to claim 2 , wherein the compound (b) is contained in the monomer composition in an amount of 0.1% by mass to 35% by mass. 4 . The adhesive according to claim 1 , wherein the monomer composition contains at least one selected from the group consisting of pyromellitic acid, pyromellitic anhydride, sorbitol, pentaerythritol, and dipentaerythritol. 5 . The adhesive according to claim 1 , wherein the polyester polyol (A1) is a reaction product of a composition containing the polycarboxylic acid, the polyol, and an isocyanate compound.

6. A laminate comprising: a first substrate; a second substrate; as well as Then, the first substrate and the second substrate are bonded together. The adhesive layer is a cured product of the adhesive according to any one of claims 1 to 5. The laminate according to claim 6 , wherein the first substrate comprises aluminum and the second substrate comprises nylon. The laminate according to claim 6 , wherein the first substrate is a barrier layer. 9 . A packaging material comprising the laminate according to claim 6 . 10 . A retort packaging material comprising the laminate according to claim 7 .

11. A non-food packaging material comprising the laminate according to claim 8.

Citation Information

Patent Citations

  • Adhesive

    JP2014101422A

  • A polyol based on dimer fatty acid residues and the corresponding polyurethanes

    CN105849151A